PENEGAKAN HUKUM TERHADAP PELAKU PENCEMARAN LINGKUNGAN HIDUP DALAM PENGELOLAAN LIMBAH INFEKSIUS COVID-19 - Agustanti, Rosalia Dika; Nasution, Ali Imran; Pratiwi, Dian Khoreanita (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2023)
Limbah infeksius Covid-19 yang tidak ditangani dengan benar dikhawatirkan menjadi sumber penularan baru Covid-19. Beberapa regulasi yang ada, diantaranya UU PPLH, UU Pengelolaan Sampah dan Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia No: P.56/Menlhk-Setjen/2015 telah memberikan pedoman cara mengelola sampah dan/atau limbah, baik itu dari rumah tangga ataupun fasilitas pelayanan kesehatan. Pengelolaan limbah infeksius Covid-19 harus dilakukan sesuai dengan peraturan perundang-undangan, namun masyarakat belum sepenuhnya mengetahui cara pengelolaan yang benar sehingga limbah yang seharusnya ditangani dengan cara khusus justru bercampur dengan limbah rumah tangga. Sehingga, diperlukan adanya aturan hukum mengenai kewajiban pengelolaan limbah infeksius Covid-19 disertai sanksi pidana, sanksi administrasi dan penambahan fasilitas pengelolaan limbah. Akhirnya, penegakan hukum terhadap pelaku pencemaran limbah infeksius Covid-19 dapat diwujudkan jika terjalin hubungan kerjasama yang baik antara masyarakat dengan pemerintah, salah satunya pemerintah menyediakan tempat pembuangan limbah infeksisus Covid-19 yang aman. Covid-19 infectious waste that is not handled properly is feared to become a new source of transmission of Covid-19. Several existing regulations, including the PPLH Law, the Waste Management Law, and the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.56/Menlhk-Setjen/2015 have provided guidelines on how to manage waste or waste, both from households and facilities. Health services. Statutory regulations must carry out the management of Covid-19 infectious waste. Still, the public needs to know how to manage it properly, so waste that should be handled specially is mixed with household waste. Thus, it is necessary to have legal regulations regarding the obligation to manage Covid-19 infectious waste accompanied by criminal sanctions, administrative sanctions, and additional waste management facilities. Finally, law enforcement against perpetrators of contamination of Covid-19 infectious waste can be realized if there is a good cooperative relationship between the community and the government, one of which is the government providing safe disposal sites for Covid-19 infectious waste.